Gipsowe zaprawy murarskie w początkach państwa polskiego - Skoczylas, Janusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2014)
The text brings attention to the role and significance of examination of rock material in the first stone buildings from the beginning of the Polish state, primarily in Poznań, Ostrów Lednicki, Gniezno, Giecz and Łekno. The most part of the text is devoted to gypsum, which, after a technological processing, was used as mortar. The natural bassets of gypsum and its waterless variety, i.e., anhydrite, can be found in the village of Wapno near Wągrowiec. It was in Wapno where this raw material was exploited and transported to construction sites. Still open remains the question of the way of transportation of this raw material from the village of Wapno to Poznań, Ostrów Lednicki, Gniezno, Giecz and Łekno.